2013
DOI: 10.1111/dom.12060
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the dipeptidyl peptidase‐4 inhibitor gemigliptin compared with sitagliptin added to ongoing metformin therapy in patients with type 2 diabetes inadequately controlled with metformin alone

Abstract: Addition of gemigliptin 50 mg daily to metformin was shown to be efficacious, well tolerated and non-inferior to sitagliptin in patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 12 publications
9
44
1
Order By: Relevance
“…25 In a metformin add-on trial performed in 425 Asian patients with inadequately controlled type 2 diabetes being treated with metformin alone, gemigliptin showed comparable efficacy and safety profiles to sitagliptin. 26 In the present study, we observed that the increased urinary excretion of 8-isoprostane after UUO, reflecting the increased oxidative stress in the kidney, was attenuated in mice treated with LC15-0444. However, we did not observe significant differences in plasma 8-isoprostane levels among the four groups.…”
Section: Discussionsupporting
confidence: 52%
“…25 In a metformin add-on trial performed in 425 Asian patients with inadequately controlled type 2 diabetes being treated with metformin alone, gemigliptin showed comparable efficacy and safety profiles to sitagliptin. 26 In the present study, we observed that the increased urinary excretion of 8-isoprostane after UUO, reflecting the increased oxidative stress in the kidney, was attenuated in mice treated with LC15-0444. However, we did not observe significant differences in plasma 8-isoprostane levels among the four groups.…”
Section: Discussionsupporting
confidence: 52%
“…At week 24, both gemigliptin treatments of 50 mg once daily and 25 mg twice daily reduced HbA 1C by 0.81 and 0.77%, respectively, which were non-inferior to 0.80% with 100 mg sitagliptin once daily. 90 The proportion of patients achieving HbA 1C < 7% with gemigliptin 25 mg twice daily (50%) or 50 mg once daily (54%) was comparable to the results with sitagliptin 100 mg once daily (49%). There were significant decreases in FPG and PPG, improvements in glucose tolerance during OGTT, and increases in GLP-1 and b-cell sensitivity to glucose in patients receiving gemigliptin treatment with their metformin therapy.…”
Section: Combination Therapymentioning
confidence: 72%
“…There were significant decreases in FPG and PPG, improvements in glucose tolerance during OGTT, and increases in GLP-1 and b-cell sensitivity to glucose in patients receiving gemigliptin treatment with their metformin therapy. 90 There was no increased risk of adverse effects with gemigliptin compared to sitagliptin 100 mg once daily.…”
Section: Combination Therapymentioning
confidence: 92%
See 1 more Smart Citation
“…For this purpose, we examined whether gemigliptin, a novel DPP-IV inhibitor developed in Korea (Rhee et al, 2013), effectively inhibits NF-κB and JNK mediated activation of inflammatory cascades through modulation of AMPK or Akt phosphorylation and subsequent reduction in the expression of vascular adhesion molecules and inflammatory cytokines in human umbilical vascular endothelial cells (HUVECs). Additionally, we evaluated whether gemigliptin treatment of macrophage-like THP-1 cells significantly reduced foam cell formation via an AMPK or Akt dependent pathway.…”
Section: Introductionmentioning
confidence: 99%